PENGUJIAN BIJI KOLEKSI KEBUN RAYA PURWODADI - Rony Irawanto (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2011)
Purwodadi Botanic Garden is a conservation institution of ex-situ plants which goes to do conservation, research, education and ecotourism activities. The main characteristic of the botanic garden is the collection of plants, some supported collections, and their documentation. Seed collection is one of the supported collection, which is responsible for handling the management of seed material collections. Seed collection as an active collection needs to be tested to know the quality of seeds during storage (viability/germination). Seeds viability activity is routinely done in the Purwodadi Botanic Gardens. This research aims to know the quality of seed collections in the Purwodadi Botanic Gardens where the result can be used as a guidance in to do the later conservation of the seed in rider to improve the quality of Purwodadi Botanic Garden collection. The stocktaking result of the plants which produce fruit and seed showed that there are 524 species from 77 genus, with a range of seed collection is around 10 – 65 species every year. Thus, seed collection viability in 2010 amounts 64 species.